This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let's do it by construction.
First, define the function f for n even:
f ( 2 ) = 1 2
f ( n ) = n − 1 n + n − 1 n ∗ f ( n − 1 ) = n − 1 n ∗ ( 1 + f ( n − 1 ) )
By induction it's easy to prove that f ( n ) = n
The question asks f ( 2 0 1 4 ) − 1 = 2 0 1 4 − 1 = 2 0 1 3 .
I get everything else but why do you have to define f for n even, and define it as f ( 2 ) = 1 2 ? Also isn't there a domain restriction on n to positive integers?
Problem Loading...
Note Loading...
Set Loading...
Notice that we can factorise the sum into 2 0 1 3 2 0 1 4 ( 1 + 2 0 1 1 2 0 1 2 ⋯ ( 1 + 1 2 ) ⋯ ) − 1
Now define then function f ( n ) = 2 n − 1 2 n ( 1 + f ( n − 1 ) ) and let f ( 1 ) = 2 . We can prove that f ( n ) = 2 n by induction as follows.
Assume that for some k , f ( k ) = 2 k this means that f ( k + 1 ) = 2 ( k + 1 ) − 1 2 ( k + 1 ) ( 1 + f ( k ) ) = 2 k + 1 2 ( k + 1 ) ( 2 k + 1 ) = 2 ( k + 1 )
therefore using f ( 1 ) = 2 as a base case we have that f ( n ) = 2 n for all positive n .
Now notice the original expression is simply f ( 1 0 0 7 ) − 1 therefore the answer is 2 × 1 0 0 7 − 1 = 2 0 1 4 − 2 = 2 0 1 3